Asprosin aggravates vascular endothelial dysfunction via disturbing mitochondrial dynamics in obesity models. Issue 3 (24th January 2023) - Lu, Yanli; Yuan, Wanwan; Xiong, Xiaowei; Huang, Qianqian; Chen, Sheng; Yin, Tingting; Zhang, Yanan; Wang, Zhie; Zeng, Guohua; Huang, Qiren
Abstract: Objective: The aim of the study was to investigate the contribution of asprosin (ASP), a fasting‐induced hormone involved in metabolic disorders, to vascular endothelial dysfunction in obesity models. Methods: Primary rat thoracic aortic endothelial cells treated with palmitic acid and mice fed with a high‐fat diet (HFD) were used as the obesity models. The role and mechanism of ASP in endothelial dysfunction were investigated by the means of morphologic, functional, and genetic analysis. Results: ASP aggravated the endothelial dysfunction induced by either palmitic acid  in vitro or an HFD in vivo, characterized as the impairment of endothelium‐dependent vasodilation, reduction of nitric oxide levels, elevation of malondialdehyde levels, and inhibition of phosphoinositide 3‐kinase–AKT–endothelial nitric oxide synthase signaling. However, adipose conditional knockout of ASP or ASP neutralization significantly alleviated the endothelial dysfunction induced by an HFD. Mechanistically, ASP enhanced mitochondrial fission, and inhibition of the fission through knockdown of dynamin‐related protein 1 (a fission‐hallmark factor) rescued the endothelial dysfunction and the disturbance to mitochondrial dynamics induced by ASP. Conclusions: The findings demonstrate that ASP causes and even exacerbates vascular endothelial dysfunction through promoting mitochondrial fission in obesity, suggesting that ASP can act as an early predictive marker of blood vessel dysfunction and become a novel potential therapeutic target for obesity‐related cardiovascular diseases.